Understanding the mechanical and interfacial properties of core–shell structured bamboo–plastic composites. Issue 10 (20th November 2015) - Xian, Yu; Wang, Cuicui; Wang, Ge; Ren, Wenhan; Cheng, Haitao
ABSTRACT: Core–shell structured bamboo–plastic composites (BPCs) were directly prepared with a single‐screw/single‐screw coextruder system. The effects of different shell layers, such as high‐density polyethylene (HDPE), bamboo pulp fiber (BPF)/HDPE, and white mud (WM)/HDPE, were studied in the context of the mechanical properties and the characteristics of the interfacial transition zone (ITZ) of BPC. The mechanical properties of the core–shell structured BPC were characterized by flexure, short‐beam shear, and impact tests. The surface morphologies of BPC were analyzed with field emission scanning electron microscopy. The ITZ properties were studied with dynamic mechanical analysis and nano‐indentation testing. The results show that the flexural properties, short‐beam strength, and impact strength decreased profoundly in the presence of BPF or WM. The dynamic mechanical analysis results suggest that the ITZ properties decreased, as indicated by the reductions in the storage modulus, loss modulus, and loss factor; the nano‐indentation results show that on the addition of BPF or WM, a gradient in the hardness and modulus of elasticity appeared across ITZ. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43053. Abstract :